Entry to Study Expectations of Science, Technology, Engineering and Mathematics Postgraduate Taught Students. (20th July 2016) - Morgan, Michelle; Direito, Inês
Abstract: There is extensive knowledge of learning and teaching behaviour and practice at undergraduate level, but limited, albeit increasing, of postgraduate taught study. The Postgraduate Experience Project (PEP) was one of 20 projects funded by the Higher Education Funding Council for England to explore ways of widening participation at postgraduate master's level. It was the largest consortium comprising of 11 universities across the UK (9 English, 1 Scottish and 1 Welsh). PEP assessed STEM postgraduate masters students' learning and teaching experiences and expectations through an online survey during Induction period (Entry to Study survey). The survey explored students' experiences of previous learning and teaching methods, their understanding of academic feedback and their preferences, as well as their expectation of learning at postgraduate taught level (PGT). This paper presents different student's experiences and expectations by groups such as gender and mode of study. The findings suggest that a 'one size fits all' learning and teaching approach to PGT students is not adequate to support the student experience due to the complexity and multiplicity of postgraduate the student's profile, background, needs and expectations.